The Sleepwalker Tonic : Nightmares! #2 - Segel, Jason, 1979-; Miller, Kirsten, 1973-; Kwasny, Karl (New York : Delacorte Press, 2015)
"Twelve-year-old Charlie and his friends must find out why their neighboring town has become overrun with sleepwalkers before what's going around reaches them and it's too late"--
Keywords: Sleepwalking -- Fiction; Dreams -- Fiction; JUVENILE FICTION / Bedtime & Dreams